A kind of adsorbent for purifying cyanide-containing waste gas and preparation method thereof
Through the preparation of modified activated carbon adsorbents and the use of plant straw and metal ion loading technology, the problems of complex preparation, high cost and poor removal effects in the existing technology are solved, and the efficient adsorption effect of cyanide-containing waste gas is achieved, and strict emission standards are met.
Patent Information
- Application Number
- CN202010702842.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-07-21
AI Technical Summary
In the prior art, the preparation method of adsorbents containing cyanide waste gas is complex, has high cost, and has a general removal effect, which cannot meet strict emission standards.
A modified activated carbon adsorbent was prepared by using plant straw as raw materials and modified by ammonia, HNO3 and 3-(mercaptopropyl)trimethoxysilane, combined with Cu, Ag, and Au ion-loaded modification.
The prepared modified activated carbon adsorbent has a high specific surface area and a good pore structure, which significantly improves the adsorption effect on cyanogenic waste gas, especially the saturated adsorption amount of acrylonitrile and hydrocyanic acid reaches about 500mg/g and 400mg/g, meeting strict emission standards.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cyanide-containing waste gas treatment, and particularly relates to an adsorbent for purifying cyanide-containing waste gas and a preparation method thereof. Background Art
[0002] Cyanide refers to a substance containing at least one cyanide group in the molecule. It is divided into organic cyanide and inorganic cyanide according to the different atoms or groups connected to the cyanide group. Industrial waste gas containing organic cyanide such as hydrocyanic acid, acrylonitrile, acetonitrile, adiponitrile, etc. is generally referred to as cyanide waste gas. Cyanide is generally highly toxic. For example, the toxicity of hydrocyanic acid is 30 times that of carbon monoxide, and the toxicity of acrylonitrile is 3 times that of carbon monoxide. Even the commonly used good organic solvent acetonitrile is a medium-toxic substance. Inhaling excessive acetonitrile will cause symptoms such as weakness, chest tightness, diarrhea, and even convulsions and coma in severe cases. Cyanide waste gas in the petrochemical industry has the characteristics of wide sources, large displacement, low concentration, and high toxicity. At the same time, it is accompanied by the emission of pollutants such as hydrocarbons, carbon monoxide, and sulfides, which causes serious pollution. Therefore, how to effectively treat cyanide waste gas is an urgent problem to be solved. At the same time, relevant national laws have also made strict requirements on the emission standards of cyanide waste gas. For example, the Petrochemical Industry Pollutant Emission Standard (GB 31571-2015) stipulates that from July 1, 2015, the permissible emission concentration of acrylonitrile shall be less than 0.5 mg / m 3 , the emission concentration of acetonitrile is less than 50mg / m 3 , the emission concentration of hydrocyanic acid is less than 1.9mg / m 3 . Emission standards are gradually increasing as environmental issues become more prominent. Adsorption is one of the main methods for purifying cyanide-containing waste gas.
[0003] Patent CN 102755876 A provides a modified activated carbon treatment method for removing hydrocyanic acid, which includes soaking the activated carbon in distilled water for 24 hours, and drying at a constant temperature of 100-110°C for 24 hours; preparing a NaOH solution with a concentration of 2%-8%; placing the dried activated carbon in the NaOH solution, stirring it magnetically, mixing it thoroughly, and then standing it for 24 hours; and drying it at a constant temperature of 100-110°C for 12 hours. Through NaOH treatment, the acidic oxygen-containing functional groups of the activated carbon can be reduced, the alkaline oxygen-containing functional groups on the surface can be increased, and the alkalinity can be improved, thereby improving the ability of the activated carbon to remove hydrocyanic acid. The temperature is 100°C, 2g of activated carbon, the initial concentration is 200ppm, the gas volume flow rate is 1000ml / min, and the outlet concentration reaches 80% of the initial concentration when penetration occurs, and the best effect is only 50min. Further improvement is needed.
[0004] Patent CN103447002 A provides an activated carbon modification method for removing hydrocyanic acid. It is mainly modified by CaCl2 solution, which can reduce the acidic oxygen-containing groups on the surface of the activated carbon, increase the alkaline oxygen-containing functional groups on the surface, reduce the acidity, and increase the alkalinity, thereby improving the ability of the activated carbon to remove hydrocyanic acid. The temperature is 100°C, 2g activated carbon, the initial concentration is 200ppm, the gas volume flow rate is 1000ml / min, and the outlet concentration reaches 80% of the initial concentration. The best effect is only 50min, and the penetration time is only 914s.
[0005] Patent CN102273730A provides a method for preparing an adsorbent for reducing hydrocyanic acid in cigarette smoke. The main component of the adsorbent is porous silica, which is prepared by doping it with aluminum oxide, magnesium oxide / calcium oxide or copper oxide. The adsorbent has the characteristic of significantly reducing hydrocyanic acid at room temperature, and the reduction rate can reach 68%.
[0006] Currently, the preparation method of adsorbents for cyanide-containing waste gas is complicated, the price is generally high, and the removal effect is average. Therefore, there is an urgent need for a new, cheaper preparation method for adsorbents that can specifically adsorb cyanide-containing waste gas. Summary of the invention
[0007] In view of the shortcomings of the prior art, one object of the present invention is to provide a modified activated carbon adsorbent with good stability and high adsorption activity for cyanide-containing waste gas. Another object is to provide a preparation method of an activated carbon adsorbent that is simple to prepare, easy to operate, and can utilize plant resources.
[0008] The present invention provides the following technical solutions:
[0009] A method for preparing an adsorbent for purifying cyanide-containing waste gas comprises the following steps:
[0010] S1. Preparation of biomass-based activated carbon using plant straw;
[0011] S2, modifying the biomass-based activated carbon obtained in step S1 using ammonia or HNO3 and 3-(mercaptopropyl)trimethoxysilane;
[0012] S3, the biomass-based activated carbon modified in step S2 is subjected to Cu, Ag, and Au ion loading modification to obtain a modified active agent, i.e., an adsorbent for purifying cyanide-containing waste gas.
[0013] Preferably, the precursor for preparing biomass-based activated carbon in step S1 is plant straw such as corn straw core, sorghum straw core, sugarcane straw core, etc., and the precursor is activated by ZnCl2 and calcined at high temperature to obtain biomass-based activated carbon. The specific steps are as follows:
[0014] (1) washing plant straw with deionized water and drying at 90-120° C. for 8-24 h, removing moisture, measuring a certain concentration of zinc chloride aqueous solution (weighing a certain mass of zinc chloride and adding it to deionized water, stirring it fully, and preparing a certain concentration of zinc chloride aqueous solution) and mixing it with the dried plant straw, placing the evenly mixed mixture into a rotary evaporator, wherein the mixture is rotated at 30-60° C. for 5-15 h under normal pressure, and dried at 90-130° C. for 8-24 h; then pyrolyzing the mixture of the dried biomass and zinc chloride, wherein the pyrolysis method is: under the protection of inert gas, heating to 400-650° C. at a rate of 10-30° C. / min, keeping the temperature for 2-5 h, and then cooling to room temperature to obtain product A;
[0015] (2) adding the product A obtained in step (1) to a dilute hydrochloric acid solution, stirring at 30-70° C. for 30 min to reduce the ash content in the activated carbon, and recovering zinc ions to obtain product B, wherein the hydrochloric acid concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L.
[0016] (3) Filter the product B obtained in step (2), and wash the filter cake with hot deionized water at 50-70° C. until the pH of the resulting solution (referring to the hot deionized water after washing) is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 60-90° C. and dried for 6-20 hours to obtain biomass-based activated carbon.
[0017] Preferably, the plant straw in step (1) is one of corn straw cores, sorghum straw cores, sugarcane straw cores, or a combination thereof; the mass fraction of zinc chloride in the zinc chloride aqueous solution in step (1) is 5-20%, and the mass of the zinc chloride aqueous solution used is 0.8-2 times the mass of the plant straw.
[0018] Preferably, the specific method of ammonia modification in step S2 is: calcining the obtained biomass-based activated carbon at 300-700° C. for 1-5 hours in a mixed atmosphere of inert gas and ammonia, and cooling it to room temperature in the inert gas atmosphere to obtain ammonia-modified biomass-based activated carbon, wherein the volume fraction of ammonia in the mixed gas of inert gas and ammonia is 20%-100%;
[0019] Preferably, the specific method of modifying HNO3 and 3-(mercaptopropyl)trimethoxysilane in step S2 is as follows:
[0020] 1) adding the obtained biomass-based activated carbon to a HNO3 solution, impregnating it at 40-60°C for 8-12h, washing the impregnated biomass-based activated carbon with deionized water until it is neutral, and drying it at 100-120°C for 10-20h to obtain a highly efficient adsorbent activated carbon;
[0021] 2) Add a certain amount of ethanol with a water content of 1%-5% to the high-efficiency adsorbent activated carbon prepared in step 1), mix evenly, and ultrasonically vibrate for 20 minutes, then add a certain amount of 3-(mercaptopropyl)trimethoxysilane, stir for 4-8 hours under nitrogen protection and 25°C, wash alternately with ethanol and deionized water 3-5 times after the reaction, then vacuum dry at 60-90°C for 2-6 hours, and cool to room temperature to obtain HNO3 and 3-(mercaptopropyl)trimethoxysilane-modified biomass-based activated carbon.
[0022] Preferably, the concentration of the HNO3 solution in step 1) is 20-30%, and 1g of biomass-based activated carbon reacts with 15-25ml of HNO3 solution.
[0023] Preferably, in step 2), 1 g of activated carbon as a high-efficiency adsorbent is added to a mixed solution of 50-100 ml of ethanol and water; 1 g of activated carbon as a high-efficiency adsorbent is added to 0.1-0.5 ml of 3-(mercaptopropyl)trimethoxysilane.
[0024] Preferably, the biomass-based activated carbon modified in step S2 is placed in a certain concentration of Cu(NO3)2, AuCl3, and AgNO3 solution, immersed for 8-24 hours, and calcined at 200-400°C in an inert atmosphere for 4-12 hours, and naturally cooled to room temperature under the protection of inert gas to obtain modified activated carbon with a metal mass content of 1-5%.
[0025] The present invention also provides an adsorbent prepared by the above preparation method and used for purifying cyanide-containing waste gas.
[0026] Preferably, the specific surface area of the modified activated carbon is 1800-2100m 2 / g (measured by BET method), and the average pore size is 1.8-2.5nm (measured by BJH method).
[0027] Beneficial effects:
[0028] 1. The present invention adopts plant straw widely existing in nature as raw material, which is low in cost, pollution-free, and easy to degrade. After ammonia modification, the acidic groups on the surface of activated carbon can be significantly reduced, the number of nitrogen-containing groups can be increased, and the loading modification of Cu, Ag, and Au ions can be facilitated. The activated carbon after ion modification has a good adsorption effect on cyanide-containing waste gas, and the saturated adsorption capacity of acrylonitrile is as high as 500mg / g, and the adsorption capacity of hydrocyanic acid is as high as 400mg / g. After HNO3 and 3-(mercaptopropyl)trimethoxysilane modification, it is conducive to the loading modification of Cu, Ag, and Au ions, and the activated carbon after ion modification has a good adsorption effect on cyanide-containing waste gas, and the saturated adsorption capacity of acrylonitrile is as high as 520mg / g, and the adsorption capacity of hydrocyanic acid is as high as 410mg / g.
[0029] 2. The carrier activated carbon of the present invention has a very high specific surface area. The activated carbon adsorbent involved in the present invention uses natural materials such as corn straw core, sorghum straw core, sugarcane straw core as raw materials, which is low in cost, pollution-free and easy to degrade. The surface area of the prepared adsorbent is 1800-2100m 2 / g (BET), ensuring the adsorption efficiency; the average pore size is 1.8-2.5nm (BJH). DETAILED DESCRIPTION
[0030] Comparative Example
[0031] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 90℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 5% zinc chloride aqueous solution. Take 200g of zinc chloride solution, that is, zinc chloride aqueous solution and mix it with biomass, put the mixed mixture into a rotary evaporator, wherein it is rotated at 60℃ for 5h under normal pressure and dried at 90℃ for 24h. The mixture of dried biomass (corn stalk core) and zinc chloride is pyrolyzed, and the pyrolysis method is specifically as follows: under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., helium is selected in this embodiment), the temperature is raised to 650℃ at a rate of 30℃ / min, and after keeping warm for 2h, it is naturally cooled to room temperature under the protection of inert gas to obtain product A.
[0032] (2) preparing a certain amount of 0.5 mol / L dilute hydrochloric acid solution, adding the product A obtained in step (1) to 100 ml of the dilute hydrochloric acid solution, stirring at 30° C. for 30 min to reduce the ash content in the activated carbon, and recovering zinc ions to obtain product B.
[0033] (3) Filter the product B obtained in step (2), and wash the filter cake with 50° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 60° C. and dried for 20 h to obtain biomass-based activated carbon.
[0034] (4) The obtained activated carbon was added to a 20% HNO3 solution and immersed at 40°C for 12 hours. The immersed activated carbon was washed with deionized water until neutral, and then dried at 100°C for 20 hours.
[0035] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a Cu(NO3)2 solution with a concentration of 1.5 mol / L, and immerse it at room temperature for 12 h. The impregnated adsorbent is calcined at 200°C for 12 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 1%.
[0036] The specific surface area of the activated carbon obtained is 1924m 2 / g (measured by BET method, hereinafter referred to as BET), and the average pore size is 2.35nm (measured by BJH method, hereinafter referred to as BJH).
[0037] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 294 mg / g.
[0038] Example 1
[0039] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 90℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 5% zinc chloride aqueous solution. Take 200g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 60℃ for 5h under normal pressure and then dries at 90℃ for 24h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 650℃ at a rate of 30℃ / min, keep warm for 2h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., nitrogen is selected in this embodiment) to obtain product A.
[0040] (2) preparing a certain amount of 0.5 mol / L dilute hydrochloric acid solution, adding the product A obtained in step (1) to 100 ml of the dilute hydrochloric acid solution, stirring at 30° C. for 30 min to reduce the ash content in the activated carbon, and recovering zinc ions to obtain product B.
[0041] (3) Filter the product B obtained in step (2), and wash the filter cake with 50° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 60° C. and dried for 20 h to obtain biomass-based activated carbon.
[0042] (4) The obtained activated carbon was added to a 20% HNO3 solution and immersed at 40°C for 12 hours. The immersed activated carbon was washed with deionized water until neutral, and then dried at 100°C for 20 hours.
[0043] (5) Add 1% ethanol with a water content (1 g of activated carbon and 50 ml of a mixed solution) to the activated carbon prepared in step (4), mix well, and ultrasonically vibrate for 20 minutes. Then add a certain amount of 3-(mercaptopropyl)trimethoxysilane (1 g of activated carbon plus 0.1 ml), stir at 25°C under nitrogen protection for 4 hours. After the reaction is completed, wash with ethanol and deionized water alternately for 3 times, and then vacuum dry at 60°C for 6 hours.
[0044] (6) Take 10 g of the adsorbent obtained in step (5) and put it into a Cu(NO3)2 solution with a concentration of 1.5 mol / L, and immerse it at room temperature for 12 h. The impregnated adsorbent is calcined at 200°C for 12 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 1%.
[0045] The specific surface area of the activated carbon obtained is 1865m 2 / g (BET), and the average pore size is 1.83nm (BJH).
[0046] The adsorption effect of the adsorbent was carried out in a fixed bed reactor, the content of acrylonitrile was 400ppm, the remaining components were air, the adsorption temperature was 25°C, the experimental air velocity was 4000h-1, and when the outlet acrylonitrile concentration was 90% of the inlet concentration, it was defined as adsorption saturation of the adsorbent, and the saturated adsorption capacity was calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon was 432mg / g.
[0047] Example 2
[0048] (1) Take 100g of sorghum straw core, wash it thoroughly with deionized water and dry it at 90℃ for 15h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 20% zinc chloride aqueous solution. Take 80g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 60℃ for 5h under normal pressure and is dried at 130℃ for 8h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is specifically as follows: under the protection of an inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., helium is selected in this embodiment), heat to 400℃ at a rate of 10℃ / min, keep warm for 5h, and naturally cool to room temperature under the protection of an inert gas to obtain product A.
[0049] (2) Prepare a certain amount of 2 mol / L dilute hydrochloric acid solution, add the product A obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 70° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0050] (3) Filter the product B obtained in step (2), and wash the filter cake with 60° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 70° C. and dried for 18 hours to obtain biomass-based activated carbon.
[0051] (4) The obtained activated carbon was added to a 30% HNO3 solution and immersed at 60°C for 8 hours. The immersed activated carbon was washed with deionized water until neutral, and then dried at 120°C for 10 hours.
[0052] (5) Add 5% ethanol with a water content (1 g activated carbon: 100 ml mixed solution) to the activated carbon prepared in step (4), mix well, and ultrasonically vibrate for 20 minutes. Then add a certain amount of 3-(mercaptopropyl)trimethoxysilane (1 g activated carbon plus 0.5 ml), stir at 25°C under nitrogen protection for 8 hours. After the reaction is completed, wash with ethanol and deionized water alternately for 5 times, and then vacuum dry at 90°C for 2 hours.
[0053] (6) Take 10 g of the adsorbent obtained in step (5) and put it into a Cu(NO3)2 solution with a concentration of 7.5 mol / L, and immerse it at room temperature for 8 h. The impregnated adsorbent is calcined at 400°C for 4 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 5%.
[0054] The specific surface area of the activated carbon obtained is 2123m 2 / g (BET), and the average pore size is 2.52nm (BJH).
[0055] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 521 mg / g.
[0056] Example 3
[0057] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 15% zinc chloride aqueous solution. Take 120g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 550℃ at a rate of 20℃ / min, keep warm for 3h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, argon is selected in this embodiment) to obtain product A.
[0058] (2) Prepare a certain amount of 1.5 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0059] (3) Filter the product B obtained in step (2), and wash the filter cake with 70° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain biomass-based activated carbon.
[0060] (4) The obtained activated carbon was added to a 25% HNO3 solution and immersed at 50°C for 10 h. The immersed activated carbon was washed with deionized water until neutral and then dried at 110°C for 15 h.
[0061] (5) Add 2% ethanol with a water content (a mixed solution of 1 g activated carbon and 60 ml) to the activated carbon prepared in step (4), mix well, and ultrasonically vibrate for 20 minutes. Then add a certain amount of 3-(mercaptopropyl)trimethoxysilane (0.4 ml for 1 g activated carbon), stir at 25°C under nitrogen protection for 6 hours. After the reaction is completed, wash with ethanol and deionized water alternately for 4 times, and then vacuum dry at 80°C for 3 hours.
[0062] (6) Take 10 g of the adsorbent obtained in step (5) and put it into a Cu(NO3)2 solution with a concentration of 3 mol / L, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 300°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 2%.
[0063] The specific surface area of the activated carbon obtained is 2102m 2 / g(BET), average pore size is 2.41nm
[0064] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 495 mg / g.
[0065] Example 4
[0066] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 10% zinc chloride aqueous solution. Take 160g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 550℃ at a rate of 20℃ / min, keep warm for 3h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., nitrogen is selected in this embodiment) to obtain product A.
[0067] (2) Prepare a certain amount of 1 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0068] (3) Filter the product B obtained in step (2), and wash the filter cake with 70° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 90° C. and dried for 6 h to obtain biomass-based activated carbon.
[0069] (4) Add the obtained activated carbon to a 30% HNO3 solution and soak it at 60°C for 12 hours. Wash the soaked activated carbon with deionized water until it is neutral, and dry it at 1120°C for 15 hours. This is the highly efficient adsorbent activated carbon.
[0070] (5) Add 3% ethanol with a water content (a mixed solution of 1 g activated carbon and 80 ml) to the activated carbon prepared in step (4), mix well, and ultrasonically vibrate for 20 minutes. Then add a certain amount of 3-(mercaptopropyl)trimethoxysilane (0.3 ml for 1 g activated carbon), stir at 25°C under nitrogen protection for 8 hours. After the reaction is completed, wash with ethanol and deionized water alternately for 4 times, and then vacuum dry at 80°C for 4 hours.
[0071] (6) Take 10 g of the adsorbent obtained in step (5) and put it into a 3 mol / L AgNO3 solution, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 400°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with an Ag content of 3%.
[0072] The specific surface area of the activated carbon obtained is 1921m 2 / g (BET), the average pore size is 2.23nm.
[0073] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of hydrocyanic acid was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet concentration of hydrocyanic acid is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 389 mg / g.
[0074] Example 5
[0075] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 15% zinc chloride aqueous solution. Take 120g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 550℃ at a rate of 20℃ / min, keep warm for 3h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., nitrogen is selected in this embodiment) to obtain product A.
[0076] (2) Prepare a certain amount of 1 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0077] (3) Filter the product B obtained in step (2), and wash the filter cake with 50° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 90° C. for 12 h to obtain biomass-based activated carbon.
[0078] (4) The obtained activated carbon was added to a 30% HNO3 solution and impregnated at 460°C for 8 hours. The impregnated activated carbon was washed with deionized water until neutral and then dried at 100°C for 18 hours.
[0079] (5) Add 4% ethanol with a water content (a mixed solution of 1 g activated carbon and 90 ml) to the activated carbon prepared in step (4), mix well, and ultrasonically vibrate for 20 minutes. Then add a certain amount of 3-(mercaptopropyl)trimethoxysilane (0.4 ml for 1 g activated carbon), stir at 25°C under nitrogen protection for 8 hours. After the reaction is completed, wash with ethanol and deionized water alternately for 4 times, and then vacuum dry at 80°C for 5 hours.
[0080] (6) Take 10 g of the adsorbent obtained in step (5) and put it into a 2.5 mol / L AuCl3 solution, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 300°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with an Au content of 5%.
[0081] The specific surface area of the activated carbon obtained is 2071m 2 / g(BET), average pore size is 2.44nm
[0082] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of hydrocyanic acid was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet concentration of hydrocyanic acid is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 410 mg / g.
[0083] Example 6
[0084] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 90℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 5% zinc chloride aqueous solution. Take 200g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 60℃ for 5h under normal pressure and then dries at 90℃ for 24h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 650℃ at a rate of 30℃ / min, keep warm for 2h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, argon is selected in this embodiment) to obtain product A.
[0085] (2) Prepare a certain amount of 0.5 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 30° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0086] (3) Filter the product B obtained in step (2), and wash the filter cake with 50° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 60° C. and dried for 20 h to obtain biomass-based activated carbon.
[0087] (4) Calcine the activated carbon obtained in step (3) at 300°C for 5 h in an ammonia atmosphere. Cool naturally to room temperature in an ammonia atmosphere. Determine the pH of the activated carbon by Boehm titration experiment pzc It is 8.2.
[0088] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a Cu(NO3)2 solution with a concentration of 1.5 mol / L, and immerse it at room temperature for 12 h. The impregnated adsorbent is calcined at 200°C for 12 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 1%.
[0089] The specific surface area of the activated carbon obtained is 1835m 2 / g (BET), and the average pore size is 1.82nm (BJH).
[0090] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 421 mg / g.
[0091] Example 7
[0092] (1) Take 100g of sugarcane straw core, wash it thoroughly with deionized water and dry it at 90℃ for 15h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 20% zinc chloride aqueous solution. Take 80g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 60℃ for 5h under normal pressure and is dried at 130℃ for 8h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is specifically as follows: under the protection of an inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., helium is selected in this embodiment), the temperature is raised to 400℃ at a rate of 10℃ / min, and after keeping warm for 5h, it is naturally cooled to room temperature under the protection of an inert gas to obtain product A.
[0093] (2) Prepare a certain amount of 2 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 70° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0094] (3) The product B obtained in step (2) is filtered, and the filter cake is thoroughly washed with deionized water at 60° C. until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 70° C. and dried for 18 hours to obtain biomass-based activated carbon.
[0095] (4) The activated carbon obtained in step (3) is calcined at 700°C for 1 hour in a mixed atmosphere of inert gas and ammonia (20% volume fraction, referring to the volume fraction of ammonia in the mixed gas). The mixture is cooled to room temperature. The pH value of the activated carbon is determined by Boehm titration experiment.pzc It is 9.7.
[0096] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a Cu(NO3)2 solution with a concentration of 7.5 mol / L, and immerse it at room temperature for 8 h. The impregnated adsorbent is calcined at 400°C for 4 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 5%.
[0097] The specific surface area of the activated carbon obtained is 2105m 2 / g (BET), and the average pore size is 2.51 nm (BJH).
[0098] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 501 mg / g.
[0099] Example 8
[0100] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 15% zinc chloride aqueous solution. Take 120g of zinc chloride solution and mix it with biomass, put the mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the temperature is raised to 550℃ at a rate of 20℃ / min under the protection of inert gas. After keeping the temperature for 3h, it is naturally cooled to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., nitrogen is selected in this embodiment) to obtain product A.
[0101] (2) Prepare a certain amount of 1.5 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0102] (3) Filter the product B obtained in step (2), and wash the filter cake with 70° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 80° C. and dried for 12 h to obtain biomass-based activated carbon.
[0103] (4) The activated carbon obtained in step (3) was calcined at 600° C. for 2 h in a mixed atmosphere of an inert gas and ammonia (40% by volume, referring to the volume fraction of ammonia in the mixed gas). The activated carbon was cooled to room temperature in the inert gas atmosphere. The pH of the activated carbon was determined by Boehm titration experiment to be 9.7.
[0104] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a Cu(NO3)2 solution with a concentration of 3 mol / L, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 300°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with a Cu content of 2%.
[0105] The specific surface area of the activated carbon obtained is 2097m 2 / g(BET), average pore size is 2.41nm
[0106] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of acrylonitrile was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet acrylonitrile concentration is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 482 mg / g.
[0107] Example 9
[0108] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 10% zinc chloride aqueous solution. Take 160g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 550℃ at a rate of 20℃ / min, keep warm for 3h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, argon is selected in this embodiment) to obtain product A.
[0109] (2) Prepare a certain amount of 1 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0110] (3) Filter the product B obtained in step (2), and wash the filter cake with 70° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 90° C. and dried for 6 h to obtain biomass-based activated carbon.
[0111] (4) Calcine the activated carbon obtained in step (3) at 500°C (600°C) for 3 h in a mixed atmosphere of inert gas and ammonia (60% volume fraction, referring to the volume fraction of ammonia in the mixed gas). Cool it to room temperature in the inert gas atmosphere. Determine the pH value of the activated carbon by Boehm titration experiment pzc It is 9.3.
[0112] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a 3 mol / L AgNO3 solution, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 400°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with an Ag content of 3%.
[0113] The specific surface area of the activated carbon obtained is 1903m 2 / g (BET), the average pore size is 2.22nm.
[0114] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of hydrocyanic acid was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet concentration of hydrocyanic acid is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 373 mg / g.
[0115] Example 10
[0116] (1) Take 100g corn stalk core, wash it thoroughly with deionized water and dry it at 120℃ for 24h. Weigh a certain mass of zinc chloride and add it to deionized water, stir it thoroughly, and prepare a 15% zinc chloride aqueous solution. Take 120g of zinc chloride solution and mix it with biomass, put the evenly mixed mixture into a rotary evaporator, where it rotates at 30℃ for 15h under normal pressure and then dries at 100℃ for 18h. The dried biomass and zinc chloride mixture is pyrolyzed, and the pyrolysis method is as follows: under the protection of inert gas, heat to 550℃ at a rate of 20℃ / min, keep warm for 3h, and then cool naturally to room temperature under the protection of inert gas (non-oxidizing gas such as nitrogen, argon, helium, etc., nitrogen is selected in this embodiment) to obtain product A.
[0117] (2) Prepare a certain amount of 1 mol / L dilute hydrochloric acid solution, add the product obtained in step (1) into 100 ml of the dilute hydrochloric acid solution, and stir at 50° C. for 30 min to reduce the ash content in the activated carbon and recover zinc ions to obtain product B.
[0118] (3) Filter the product B obtained in step (2), and wash the filter cake with 50° C. deionized water until the pH of the resulting solution is equal to 7. The resulting activated carbon is placed in a vacuum drying oven at 90° C. for 12 h to obtain biomass-based activated carbon.
[0119] (4) The activated carbon obtained in step (3) is calcined at 400°C for 4 hours in a mixed atmosphere of inert gas and ammonia (80% volume fraction, referring to the volume fraction of ammonia in the mixed gas). The activated carbon is cooled to room temperature in the inert gas atmosphere. The pH value of the activated carbon is determined by Boehm titration experiment. pzc It is 8.8.
[0120] (5) Take 10 g of the adsorbent obtained in step (4) and put it into a 2.5 mol / L AuCl3 solution, and immerse it at room temperature for 18 h. The impregnated adsorbent is calcined at 300°C for 8 h in an inert atmosphere, and naturally cooled to room temperature under the protection of an inert gas to obtain a modified activated carbon with an Au content of 5%.
[0121] The specific surface area of the activated carbon obtained is 2057m 2 / g(BET), average pore size is 2.41nm
[0122] The adsorption effect of the adsorbent was carried out in a fixed bed reactor. The content of hydrocyanic acid was 400 ppm, the remaining components were air, the adsorption temperature was 25 °C, and the experimental air velocity was 4000 h -1 When the outlet concentration of hydrocyanic acid is 90% of the inlet concentration, the adsorbent is defined as saturated, and the saturated adsorption capacity is calculated based on this. Under this reaction condition, the saturated adsorption capacity of the prepared modified activated carbon is 401 mg / g.
[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an adsorbent for purifying cyanide-containing waste gas, characterized in that: The following steps are involved: S1. Preparation of biomass-based activated carbon using plant straw; S2, modifying the biomass-based activated carbon obtained in step S1 using ammonia; S3, performing Cu, Ag or Au ion loading modification on the biomass-based activated carbon modified in step S2 to obtain modified activated carbon, i.e., an adsorbent for purifying cyanide-containing waste gas; Step S1 The specific steps of preparing biomass-based activated carbon are as follows: (1) washing the plant straw with deionized water and drying it at 90-120° C. for 8-24 h, removing moisture, measuring a certain concentration of zinc chloride aqueous solution and mixing it with the dried plant straw, placing the uniformly mixed mixture into a rotary evaporator, rotary evaporating it at 30-60° C. for 5-15 h under normal pressure, and drying it at 90-130° C. for 8-24 h; then pyrolyzing the mixture of the dried plant straw and zinc chloride, the pyrolysis method being: under the protection of inert gas, heating to 400-650° C. at a rate of 10-30° C. / min, keeping the temperature for 2-5 h, and then cooling to room temperature to obtain product A; (2) adding the product A obtained in step (1) to a dilute hydrochloric acid solution, stirring at 30-70° C. for 30 min, and recovering zinc ions to obtain a product B, wherein the hydrochloric acid concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L; (3) filtering the product B obtained in step (2), washing the filter cake with hot deionized water at 50-70° C. until the pH of the washed solution is equal to 7, and drying the obtained filter cake in a vacuum drying oven at 60-90° C. for 6-20 h to obtain biomass-based activated carbon; The plant straw in step (1) is one of corn straw cores, sorghum straw cores, and sugarcane straw cores, or a combination thereof; the mass fraction of zinc chloride in the zinc chloride aqueous solution in step (1) is 5-20%, and the mass of the zinc chloride aqueous solution used is 0.8-2 times the mass of the plant straw; The specific method of ammonia modification in step S2 is: The obtained biomass-based activated carbon is calcined at 300-700° C. for 1-5 hours in a mixed atmosphere of inert gas and ammonia, and the temperature is lowered to room temperature in the inert gas atmosphere to obtain ammonia-modified biomass-based activated carbon, wherein the volume fraction of ammonia in the mixed atmosphere of inert gas and ammonia is 20%-100%, and is not 100%; The specific method of Cu, Ag or Au ion loading modification in step S3 is: The biomass-based activated carbon modified in step S2 is placed in a certain concentration of Cu(NO3)2, AuCl3 or AgNO3 solution, immersed for 8-24 hours, and calcined at 200-400°C in an inert atmosphere for 4-12 hours, and naturally cooled to room temperature under the protection of inert gas to obtain modified activated carbon with a metal mass content of 1-5%.
2. A method for preparing an adsorbent for purifying cyanide-containing waste gas, characterized in that: The following steps are involved: S1. Preparation of biomass-based activated carbon using plant straw; S2, modifying the biomass-based activated carbon obtained in step S1 using HNO3 and 3-(mercaptopropyl)trimethoxysilane; S3, performing Cu, Ag or Au ion loading modification on the biomass-based activated carbon modified in step S2 to obtain modified activated carbon, i.e., an adsorbent for purifying cyanide-containing waste gas; Step S1 The specific steps of preparing biomass-based activated carbon are as follows: (1) washing the plant straw with deionized water and drying it at 90-120° C. for 8-24 h, removing moisture, measuring a certain concentration of zinc chloride aqueous solution and mixing it with the dried plant straw, placing the uniformly mixed mixture into a rotary evaporator, rotary evaporating it at 30-60° C. for 5-15 h under normal pressure, and drying it at 90-130° C. for 8-24 h; then pyrolyzing the mixture of the dried plant straw and zinc chloride, the pyrolysis method being: under the protection of inert gas, heating to 400-650° C. at a rate of 10-30° C. / min, keeping the temperature for 2-5 h, and then cooling to room temperature to obtain product A; (2) adding the product A obtained in step (1) to a dilute hydrochloric acid solution, stirring at 30-70° C. for 30 min, and recovering zinc ions to obtain a product B, wherein the hydrochloric acid concentration of the dilute hydrochloric acid solution is 0.5-2 mol / L; (3) filtering the product B obtained in step (2), washing the filter cake with hot deionized water at 50-70° C. until the pH of the washed solution is equal to 7, and drying the obtained filter cake in a vacuum drying oven at 60-90° C. for 6-20 h to obtain biomass-based activated carbon; The plant straw in step (1) is one of corn straw cores, sorghum straw cores, and sugarcane straw cores, or a combination thereof; the mass fraction of zinc chloride in the zinc chloride aqueous solution in step (1) is 5-20%, and the mass of the zinc chloride aqueous solution used is 0.8-2 times the mass of the plant straw; The specific modification method using HNO3 and 3-(mercaptopropyl)trimethoxysilane in step S2 is: The obtained biomass-based activated carbon is added to a HNO3 solution, immersed at 40-60°C for 8-12h, the immersed biomass-based activated carbon is washed with deionized water until the pH is equal to 7, and dried at 100-120°C for 10-20h to obtain a high-efficiency adsorbent activated carbon; a certain amount of ethanol with a water content of 1%-5% is added to the high-efficiency adsorbent activated carbon, mixed evenly, and ultrasonically vibrated for 20min, and then a certain amount of 3-(mercaptopropyl)trimethoxysilane is added, stirred for 4-8h under nitrogen protection and 25°C, and after the reaction is completed, it is washed alternately with ethanol and deionized water for 3-5 times, and then vacuum dried at 60-90°C for 2-6h, and cooled to room temperature to obtain HNO3 and 3-(mercaptopropyl)trimethoxysilane-modified biomass-based activated carbon; The specific method of Cu, Ag or Au ion loading modification in step S3 is: The biomass-based activated carbon modified in step S2 is placed in a certain concentration of Cu(NO3)2, AuCl3 or AgNO3 solution, immersed for 8-24 hours, and calcined at 200-400°C in an inert atmosphere for 4-12 hours, and naturally cooled to room temperature under the protection of inert gas to obtain modified activated carbon with a metal mass content of 1-5%.
3. The preparation method according to claim 2, characterized in that: The concentration of the HNO3 solution in step S2 is 20-30%; 1 g of biomass-based activated carbon reacts with 15-25 ml of the HNO3 solution.
4. The preparation method according to claim 2, characterized in that: In step S2, 50-100 ml of ethanol with a water content of 1%-5% is added to 1 g of activated carbon as a high-efficiency adsorbent; and 0.1-0.5 ml of 3-(mercaptopropyl)trimethoxysilane is added to 1 g of activated carbon as a high-efficiency adsorbent.
5. An adsorbent for purifying cyanide-containing waste gas prepared by the preparation method of claim 1 or 2.
6. The adsorbent for purifying cyanide-containing waste gas prepared according to claim 5, characterized in that: The specific surface area of modified activated carbon is 1800-2100m 2 / g, and the average pore size is 1.8-2.5nm.
Citation Information
Patent Citations
An adsorbent for reducing hydrogen cyanide in mainstream cigarette smoke and its preparation method
CN102273730A
Modification treatment method of activated carbon for removing hydrocyanic acid
CN102755876A
Active carbon modification method for removing hydrocyanic acid
CN103447002A
Biomass activated carbon, preparation method thereof and application thereof in flue gas mercury removal
CN102515162A
Amino modified alkali metal base CO2 adsorbing agent and preparation method thereof
CN108392942A